Electrically controllable diffractive optical elements fabricated by direct laser writing on a carbon nanotube network film - Min, Taeyol; Yim, Jong Hyuk; Park, Sungmin; Ha, Seongju; Lee, Soonil; Yeom, Dong Il (Nanophotonics, 2023)
A randomly connected single-walled carbon nanotube (CNT) network film is suggested as an optically homogenous thin film to implement a tunable diffractive optical element with a subwavelength thickness. A Fresnel zone plate (FZP) as a thin-film lens is successfully realized by mask-free direct laser writing onto the CNT network film with a thickness of 450 nm. The fabricated FZP exhibits an intense three-dimensional focus having lateral and axial focal sizes of 0.95λ and 7.10λ, respectively, at the wavelength of 1550 nm. Furthermore, we show that the intensities at focal points of the first and second diffraction orders can be significantly modulated by 72% and 40% through ion-gel gating between +1.8 V and -1.8 V. These results may offer the potential for electro-optic tunability in multifocal diffraction flat optics and the like.
Keywords: A-carbon; Carbon nanotube network film; Carbon nanotube network; Direct laser writing; Fresnel zone plate; Single-walled carbon nanotube networks; Thin-film lens; Thin-films; Tunable thin film lens; Tunable thin films; carbon nanotube (CNT) network film; diffractive optical elements; Fresnel zone plates; tunable thin film lens